Influência da nanoargila (O-MMT) nas propriedades mecânicas de polipropileno reforçado com fibra de vidro - Arroyave, Gabriel Jaime Peláez (Universidade Federal de São Carlos, 2014)
Hybrid filler reinforced thermoplastics composed with short glass fiber (GF) and different particulate fillers present special interest for engineering applications, as substantial reductions in mechanical anisotropy and molding warpage are expected from these systems as compared to the same characteristics inherent to binary composites with GF only. These improvements are achieved by the partial substitution of GF by particulate fillers and are attained at the cost of minor reductions in rigidity, strength and toughness properties of these ternary composites. However, when nanoscale fillers such as nanoclay (NC) are incorporated in GF-reinforced thermoplastics, the mechanical strength properties of these systems are severely affected, even at very low NC content. Thus in this work, using model GF-reinforced polypropylene (PP) composites with varying total and relative concentrations of GF and organophylic montmorillonite clay (O-MMT) along with maleated PP as compatibilizer were twin-screw extrusion compounded with three different mixing protocols, in order to identify the factors leading to the observed loss in mechanical strength properties. Using tensile, flexural, izod impact and dynamic-mechanical (DMTA) characterization tests and electron microscopy (SEM and TEM) elucidation of the fiber-matrix interface/interphase microstructure, it is concluded that the physical presence of NC particles at the interface contributes towards the reduction of interfacial interactions. As a consequence of low interfacial adhesion between the nanoclay and polymeric matrix, debonding of the particles and the PP during mechanical testing occurs, leading to crack growth that anticipates ternary hybrid composites failure in stress levels lesser compared with that of binary composites. These hypotheses were corroborated by SEM and TEM analyses.
Influence of nanoclay (O-MMT) on the mechanical properties of glass fiber reinforced polypropylene
Keywords: Compósitos; Materiais híbridos; Nanocompósitos; Compatibilização interfacial; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA